Terorisme: Perspektif Barat dan Islam - Mohd. Hefzan; Fitria Fitria (SISI LAIN REALITA, 2017)
The issue of terrorism has tapped the border of human civilization. The West has a viewon terrorism following their own perceptions. Now the Western world is afraid of theirown shadows after the entry into force of the events of September 11, 2001 which haveembodied the World Trade Center (WTC) in New York. This black event has reallyshocked the Western world which so far they are proud that the United States is thegreat power of the world, has now been attacked so extreme. The problem that arisesnow in the Islamic world is that the West has misinterpreted what is said to be jihad.The enemy of Islam has labeled terrorism as a jihad in Islam, this is how the West triesto put Islam as a ferocious religion. The term jihad is what terrorism says for the West.In Islamic teachings jihad cases are something that is highly demanded and has nodirect connection with terrorism activities.